Some Global Properties of Almost Pseudo Ricci Symmetric Manifolds Satisfying Codazzi Type of Ricci Tensor - Abul Kalam Mondal (International Journal of Mathematics And its Applications, 2019)
The object of the present paper is to study some global properties of almost pseudo Ricci symmetric manifold satisfying Codazzi type of Ricci tensor. Among others, it is proved that if a compact, orientable $A(PRS)_n$ satisfying Codazzi type of Ricci tensor without boundary admits a non-isometric conformal transformation, then the $A(PRS)_n$ is isometric to a sphere. Also we obtain a sufficient condition for a compact, orientable $A(PRS)_n$ satisfying Codazzi type of Ricci tensor without boundary to be conformal to a sphere in $E_{n+1}$.